Are women the New Men? Travelling the Paths toward Internationalization of Women Executives - Gosadan, Beatriz (JPAIR Multidisciplinary Research, 2018)
History would tell us categorically that women in the past were relegated to the background. However, the 21st century has changed the lives of women in the workplace arena where they were elevated on an enviable pedestal in leadership, management, education and skills training.  This paper focused on describing the workplace challenges, opportunities and insights of women executives in Kidapawan City. Using phenomenological research design, multiple frameworks in data collection (friendly conversations, reflection analysis, and on-line interview) data analysis through story-telling writing helped me drew several themes which established the data's trustworthiness regarding credibility, transferability, dependability and confirmability. With better portrayal on their professional development, the 15 women executives welcome the opportunities traveling the paths, climbing the traditional ladders, and running down their companies, there is one constant at them: they cultivated their success. They have enjoyed opportunities brought about by professional credibility, great sense of responsibility, and most importantly, financial independence. They have faced the challenges in leadership, human behavior, and high expectations, however, family and work-life balance remain the biggest issue that has affected them emotionally. It was through prayers and family support that these women drew strength from. Hence, even if they were judged by society as weak, they continue to inspire the world.
Keywords: Multicultural; challenges and opportunities; qualitative design; Kidapawan City; Philippines